TNFa-e microsatellite, HLA-DRB1 and-DQB1 alleles and haplotypes in Brazilian patients presenting recently diagnosed type 1 diabetes mellitus - Rassi, Diane M.; Wastowski, Isabela J.; Simoes, Renata T.; Rodrigues, Sandra; Deghaide, Neife N. H. S.; Mendes-Junior, Celso T.; Simoes, Aguinaldo L.; Soares, Christiane Pienna [UNESP]; Passos, Geraldo A. S.; Donadi, Eduardo A. (Blackwell Publishing, 2006)
TNF microsatellite and HLA class II polymorphisms were studied in 28 recently diagnosed Brazilian patients presenting type 1 diabetes mellitus (T1DM) and in 120 healthy controls. TNFa-e and HLA-DRB1/DQB1 alleles were identified using sets of sequence-specific primers. Compared to controls, the DRB1* 03 and DQBI*02 allele groups, TNFa1 allele, and the TNFa4-b5-c1-d4-e3 and TNFa10-b5-c1-d4-e3 haplotypes were overrepresented in patients. TNF microsatellite together with HLA polymorphisms is associated with type 1 diabetes in Brazilian patients, corroborating the participation of the MHC genes in disease susceptibility.
Keywords: type 1 diabetes mellitus; polymorphism; TNF microsatellite; HLA